The Content of the Pedagogical Process to Develop the Knowledge of Future Physical Education Teachers About Sports Tourism - Muzaffa, Boltayeva Sumbula (Research Parks Publishers, 2023)
This article describes the peculiarities of training future physical education teachers for sports tourism, opinions on the development of various reforms in society.